Optimal allocation of mobile device sound resources for game programming purposes - Wrzos, Arkadiusz; Smołka, Jakub (Journal of Computer Sciences Institute, 2016)
Android is a mobile device platform, whose resources are limited. Games, and high-performance applications need special approach. Most of programming patterns allow for static memory allocation or maintaining low processor usage. Regardless, there are still many situations, in which development is demanding task, and needs much research. In this work author studied and research for efficient allocation of audio resources to play them with minimal latency in non deterministic way.